2017
DOI: 10.1016/j.chiabu.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about child abuse and neglect patterns of co-occurrence? A systematic review of profiling studies and recommendations for future research

Abstract: Latent class (LCA) and latent profile (LPA) analysis represent methodological approaches to identify subgroups of maltreated individuals. Although research examining child abuse and neglect (CAN) profiles is still rare, the application of person-centered techniques to clarify CAN types co-occurrence has substantially increased in recent years. Therefore, the aim of the present study was to provide a summary and critical evaluation of the findings of LCA/LPA child maltreatment research to: (a) systemize the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
107
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 71 publications
(130 reference statements)
3
107
1
2
Order By: Relevance
“…In considering the above as well as the overall paucity of CM profiling studies, Debowska, Willmott, Boduszek, and Jones (2017), in a recent review of such literature, recommended further research utilizing more diverse samples, especially those drawn from non-Western societies and exclusively female samples, to build a better understanding of CM and its consequences worldwide. Additionally, to enable the development of more targeted preventive measures, Debowska et al suggested that future profiling studies should account for the setting in which victimization was experienced (e.g., within and outside the family).…”
Section: Interactive Effects Of CM Typesmentioning
confidence: 99%
“…In considering the above as well as the overall paucity of CM profiling studies, Debowska, Willmott, Boduszek, and Jones (2017), in a recent review of such literature, recommended further research utilizing more diverse samples, especially those drawn from non-Western societies and exclusively female samples, to build a better understanding of CM and its consequences worldwide. Additionally, to enable the development of more targeted preventive measures, Debowska et al suggested that future profiling studies should account for the setting in which victimization was experienced (e.g., within and outside the family).…”
Section: Interactive Effects Of CM Typesmentioning
confidence: 99%
“…Further, extant research reports a significant association between adverse childhood experiences and externalising as well as internalising problems in adolescence and adulthood (see Debowska, Willmott, Boduszek, & Jones, 2017 for a review).…”
mentioning
confidence: 99%
“…Similar limitations, however, are common to maltreatment research and reflect the characteristics of maltreated samples. Types of abuse often co-occur, and physical or sexual abuse seldom occurs in the absence of neglect or outside of families at higher risk for spousal violence (Bidarra et al, 2016; Debowska et al, 2017; Dube et al, 2002; Schilling et al, 2016). Similarly, in the US, females are more likely to be victimized than males (Goverment, 2015).…”
Section: Discussionmentioning
confidence: 99%